Solar and Stellar Magnetic Activity. - Schrijver, Carolus J. (Cambridge Astrophysics Series, 34., 2003)
The first comprehensive review and synthesis of current understanding of magnetic fields in the Sun and similar stars. Combines studies of the Sun with those of other stars to arrive at an illuminating new view of stellar magnetic activity. Ideal for graduate students and researchers.